Dry gel electrolyte for aqueous battery as well as preparation method and application of dry gel electrolyte

By using nanosilicon dioxide in aqueous batteries to form dry glued electrolytes, the problems of narrow electrochemical windows, severe side reactions and inability to work properly at low temperatures are solved, and higher cycle stability and service life are achieved, as well as good working ability at low temperatures.

CN119650889APending Publication Date: 2025-03-18YANCHENG INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411731673.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing water-based batteries have narrow electrochemical windows, severe side reactions of the electrodes, poor cycle stability, and inability to work properly at low temperatures, which limit their application prospects.

Method used

By adding nanosilicon dioxide to the aqueous solution of the electrolyte salt, a gel electrolyte is formed, and a glued electrolyte is obtained by freeze-drying, which is embedded on the positive, negative electrode or separator of the battery.

Benefits of technology

This method effectively broadens the electrochemical window of water-based batteries, improves its conductivity and capacity retention at room temperature and low temperature, and improves cycle stability, service life and working ability at low temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650889A_ABST
    Figure CN119650889A_ABST
Patent Text Reader

Abstract

The invention discloses a dry gel electrolyte for a water-based battery and a preparation method and application thereof, and particularly relates to the technical field of water-based batteries, the preparation method comprises the following steps: putting 1.5 g of hydrophilic nano silicon dioxide with the particle size of 10-30nm and the specific surface area of 150m < 2 > / g into 10ml of aqueous solution of electrolyte salt with the solute ratio of 0.5-3mol / L, and stirring uniformly; uniformly stirring to obtain an aqueous gel-state electrolyte; the preparation method comprises the following steps: mixing hydrophilic nano silicon dioxide and sodium sulfate at a low temperature, and freeze-drying the obtained aqueous gel-state electrolyte in a freeze-drying machine until the moisture does not change any more to obtain the dry-gel-state electrolyte for the aqueous battery, so that the dry-gel-state electrolyte for the aqueous battery is obtained by mixing the hydrophilic nano silicon dioxide and the sodium sulfate and freeze-drying at the low temperature; the electrolyte has better conductivity and capacity retention ratio at normal temperature or low temperature, the electrochemical window of the electrolyte is effectively improved, the cycling stability of the aqueous battery is improved, the service life of the aqueous battery is prolonged, and the working capability of the aqueous battery at low temperature is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of aqueous batteries, and more specifically, to a dry colloidal electrolyte for aqueous batteries and a preparation method and application thereof. Background Art

[0002] Existing lithium-ion batteries and sodium-ion batteries have the characteristics of high energy density, but because they use a large amount of flammable organic electrolytes, they are prone to safety accidents during production and use, and it is difficult to meet the technical requirements of large-scale energy storage for safety and stability. Aqueous batteries are secondary batteries with water as electrolyte. They have the advantages of high safety, environmental friendliness and high ion conductivity. They have great application prospects in large-scale electrical energy storage, but are currently mainly limited by shortcomings such as narrow window voltage, side reactions at electrodes and poor cycle stability.

[0003] In aqueous batteries, due to the relatively active chemical properties of water, the theoretical decomposition voltage is only 1.23V, which greatly limits the selection of positive and negative electrode materials for aqueous batteries and the improvement of energy density. When the oxidation potential of the positive electrode and the reduction potential of the negative electrode exceed the electrochemical window of water during battery operation, water electrolysis will occur, decomposing to produce oxygen and hydrogen. This side reaction is an irreversible process in the battery, which not only creates safety hazards, but also reduces the efficiency of the battery, continuously consumes the electrolyte in the battery, affects the cycle stability of the positive and negative electrode materials, and reduces the service life of the battery. In addition, the freezing of water at low temperatures causes the battery system to fail to work properly, which also hinders the development and application of aqueous batteries. Summary of the invention

[0004] In order to overcome the above-mentioned defects of the prior art, the embodiments of the present invention provide a dry colloidal electrolyte for an aqueous battery and a preparation method and application thereof. The technical problem to be solved by the present invention is: how to effectively improve the electrochemical window of the electrolyte, and enhance the cycle stability, service life and working ability of the aqueous battery at low temperatures.

[0005] To achieve the above object, the present invention provides the following technical solution: a method for preparing a dry colloidal electrolyte for an aqueous battery, comprising: placing 1.5 g of nano-silicon dioxide into 10 ml of an aqueous solution of an electrolyte salt with a solute ratio of 0.5-3 mol / L, and uniformly stirring to obtain an aqueous gel electrolyte; placing the obtained aqueous gel electrolyte in a freeze dryer for freeze drying, and obtaining a dry colloidal electrolyte for an aqueous battery after the water content no longer changes.

[0006] In a preferred embodiment, the electrolyte salt is one or more of sodium sulfate, sodium nitrate, sodium perchlorate, lithium sulfate, lithium nitrate, lithium perchlorate, zinc sulfate, zinc nitrate, and zinc perchlorate.

[0007] In a preferred embodiment, the particle size of nano-silicon dioxide is in the range of 5 nm-500 nm.

[0008] In a preferred embodiment, the particle size of nano-silicon dioxide is in the range of 10 nm to 30 nm.

[0009] In a preferred embodiment, the nano-silica is hydrophilic nano-silica.

[0010] In a preferred embodiment, the freeze dryer is used for drying at a temperature of -20°C and the freeze drying time is 8 hours.

[0011] An aqueous dry colloidal electrolyte prepared by the above-mentioned preparation method.

[0012] An application of the above-mentioned aqueous dry gel electrolyte in the preparation of an aqueous battery, wherein the aqueous dry gel electrolyte is embedded in the positive and negative electrodes or the diaphragm of the battery.

[0013] Technical effects and advantages of the present invention:

[0014] The present invention adds nano silicon dioxide to an aqueous solution of an electrolyte salt to obtain a gel electrolyte, and freeze-dries the gel electrolyte to a dry colloidal powder. Since the dry colloidal electrolyte does not contain free water, the adverse effects caused by the decomposition of free water in the electrochemical process can be effectively avoided, and the voltage window of the aqueous battery can be effectively widened. The dry colloidal electrolyte has good conductivity and capacity retention rate both at room temperature and at low temperature, effectively improving the electrolyte electrochemical window, and enhancing the cycle stability, service life and working ability of the aqueous battery at low temperatures. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] The accompanying drawings are used to provide further understanding of the technical solutions of the present invention and constitute a part of the present invention. The embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0016] Figure 1 The charge and discharge curves of different batteries at room temperature 25°C.

[0017] Figure 2 The charge and discharge curves of different batteries at -20°C.

[0018] Figure 3 This is the cycling performance diagram of aqueous sodium ion battery at 25°C.

[0019] Figure 4 Cyclic voltammograms of different electrolytes / solutions.

[0020] Figure 5 is the AC impedance spectra of different electrolytes / liquids.

[0021] Figure 6 Graph showing the ionic conductivity of dry colloidal electrolytes made from silica with different particle sizes. DETAILED DESCRIPTION

[0022] Example embodiments will now be described more fully with reference to the accompanying drawings. However, example embodiments can be implemented in a variety of forms and should not be construed as limited to the examples set forth herein; rather, these example embodiments are provided so that the description of the present disclosure will be more comprehensive and complete and the concepts of the example embodiments will be fully conveyed to those skilled in the art. The accompanying drawings are only schematic illustrations of the present disclosure and are not necessarily drawn to scale. The same reference numerals in the figures represent the same or similar parts, and thus their repeated description will be omitted.

[0023] In addition, the described features, structures or characteristics may be combined in one or more example embodiments in any suitable manner. In the following description, many specific details are provided to provide a full understanding of the example embodiments of the present disclosure. However, those skilled in the art will appreciate that the technical solutions of the present disclosure may be practiced while omitting one or more of the specific details, or other methods, components, steps, etc. may be adopted. In other cases, well-known structures, methods, implementations or operations are not shown or described in detail to avoid obscuring various aspects of the present disclosure.

[0024] The present invention designs the following group of examples to verify the feasibility of the scheme.

[0025] Because different battery systems use different electrolyte salts, such as lithium salts for lithium batteries, sodium salts for sodium batteries, and zinc salts for zinc batteries, this application uses sodium salts as an example for illustration.

[0026] Example 1

[0027] Preparation of dry colloidal electrolyte: 1.5 g of particle size 10 nm-30 nm, specific surface area 150 m 2 / g of hydrophilic nano-silica is put into 10ml of an aqueous solution of sodium sulfate with a solute ratio of 1mol / L, and stirred evenly to obtain an aqueous gel electrolyte. The solution is placed in a freeze dryer and when the water content no longer changes, a dry gel electrolyte for aqueous batteries can be obtained.

[0028] Preferably, the uniform stirring time is 1 hour.

[0029] Preferably, the mixture is placed in a freeze dryer and freeze-dried at -20°C for 8 hours.

[0030] It should be noted that the hydrophilicity of nano-silica determines whether the silica can be well dispersed in water to form an initial gel. If it is not hydrophilic, only a suspension will be formed and no gel can be formed. Therefore, hydrophilicity is an indispensable feature of the technical means of the present invention.

[0031] Preparation of aqueous sodium-ion battery: Place aqueous dry colloidal electrolyte between the positive and negative electrodes. 0.44 MnO2, the negative electrode uses NaTi2(PO4)3 as the active material, acetylene black as the conductive agent, and PTFE as the binder to assemble an aqueous sodium ion battery.

[0032] Comparative Example 1

[0033] Preparation of ordinary aqueous electrolyte: Dissolve 142g of sodium sulfate in 1L of deionized water to obtain a Na2SO4 electrolyte with a solute ratio of 1 mol / L.

[0034] Preparation of aqueous sodium-ion battery: Place the separator between the positive and negative electrodes, and drip 1 mol / L Na2SO4 electrolyte on the separator. 0.44 MnO2, the negative electrode uses NaTi2(PO4)3 as the active material, acetylene black as the conductive agent, and PTFE as the binder, which are assembled to obtain an aqueous sodium ion battery.

[0035] Comparative Example 2

[0036] Preparation of aqueous gel electrolyte: 1.5g of particle size 10nm-30nm, specific surface area 150m 2 / g of hydrophilic nano-silica is put into 10ml of an aqueous solution containing 1mol / L sodium sulfate and stirred evenly to obtain an aqueous gel electrolyte.

[0037] Preferably, the uniform stirring time is 1 hour.

[0038] Preparation of aqueous sodium-ion battery: Place aqueous dry colloidal electrolyte between the positive and negative electrodes. 0.44 MnO2, the negative electrode uses NaTi2(PO4)3 as the active material, acetylene black as the conductive agent, and PTFE as the binder, which are assembled to obtain an aqueous sodium ion battery.

[0039] The feasibility verification test is as follows:

[0040] Charge and discharge test: Set the current density to 1C (1C = 100mA g -1 ), the charge and discharge cut-off voltage is 0.5~1.5V, and the test temperatures are room temperature 25℃ and -20℃ respectively.

[0041] Voltage window and ion conductivity test: Place the aqueous dry colloidal electrolyte between two stainless steel sheets and assemble into a symmetrical cell for voltage window and ion conductivity test.

[0042] The test results are as follows:

[0043] Figure 1 The charge and discharge curves of different batteries at room temperature 25°C show that the aqueous sodium ion battery with dry colloidal electrolyte corresponding to Example 1 can operate normally, with a charge and discharge efficiency of 97.2% in the first cycle and a discharge capacity of 55.3 mA·g -1 The charge and discharge efficiency of the aqueous sodium ion battery in comparative example 1 was 89.7% in the first cycle, and the discharge capacity was 52.9 mA g -1 The aqueous sodium ion battery with gel electrolyte in Comparative Example 2 can also operate normally, with a charge and discharge efficiency of 93.7% and a discharge capacity of 54.1 mA g -1 .

[0044] Figure 2 The charge and discharge curves of different batteries at -20°C show that the first cycle discharge capacity of the aqueous sodium ion battery with dry colloidal electrolyte in Example 1 is still 51.1 mA·g -1 The first cycle discharge capacity of the aqueous sodium ion battery in comparative example 1 is only 20.2 mA g -1 , the polarization is large, and the energy efficiency is very low. The first cycle discharge capacity of the aqueous sodium ion battery with gel electrolyte in Comparative Example 2 is only 27.2 mA g -1 , the polarization is large and the energy efficiency is low.

[0045] Figure 3 The figure is a cycle performance diagram of an aqueous sodium ion battery at 25°C. After 1000 cycles, the capacity of the aqueous sodium ion battery with dry gel electrolyte of Example 1 is 51.8 mAh / g, and the capacity retention rate is 93.6%. After 620 cycles, the capacity of the aqueous sodium ion battery of Comparative Example 1 is almost 0. After 1000 cycles, the capacity of the aqueous sodium ion battery with gel electrolyte of Comparative Example 2 is only 26.6 mAh / g, and the capacity retention rate is 49.2%.

[0046] Figure 4 The cyclic voltammograms of different electrolytes / liquids show that the dry colloidal electrolyte of Example 1 has the widest voltage window. The aqueous electrolyte of Comparative Example 1 has the lowest voltage window. The gel electrolyte of Comparative Example 2 has a voltage window between the aqueous electrolyte and the dry colloidal electrolyte.

[0047] Figure 5The AC impedance spectra of different electrolytes / liquids show that the internal resistance of the dry gel electrolyte of Example 1 increases slightly, but the ionic conductivity is still relatively high. The electrolyte of Comparative Example 1 has no obvious advantage in ionic conductivity. The gel electrolyte of Comparative Example 2 has no obvious advantage in ionic conductivity.

[0048] From the above comparison, it can be seen that the aqueous dry colloidal electrolyte obtained by mixing and drying the clear water type nano-silica and sodium sulfate has the advantage of stable operation at room temperature and low temperature, and can still have an objective capacity retention rate after multiple cycles.

[0049] Therefore, the present invention obtains a dry colloidal electrolyte by mixing hydrophilic nano-silica and sodium sulfate and freeze-drying them at low temperature. The electrolyte has good conductivity and capacity retention rate both at room temperature and at low temperature, effectively improving the electrolyte electrochemical window, and enhancing the cycle stability, service life and working ability of aqueous batteries at low temperatures.

[0050] Figure 6 The ionic conductivity diagram of dry colloidal electrolytes made from silica with different particle sizes. From the figure, it can be seen that when the particle size of nano-silica is in the range of 10nm-30nm, especially at 20nm, the battery prepared has the highest ionic conductivity and the strongest activity, and the ionic conductivity continues to decrease thereafter.

[0051] The above description is only by way of illustration of certain exemplary embodiments of the present invention. It is undoubted that those skilled in the art can modify the described embodiments in various ways without departing from the spirit and scope of the present invention. Therefore, the above drawings and descriptions are illustrative in nature and should not be construed as limiting the scope of protection of the claims of the present invention.

[0052] Finally, a few points should be explained: First, in the description of this application, it should be noted that, unless otherwise specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, which may refer to mechanical connection or electrical connection, or internal communication between two components, or direct connection. "upper", "lower", "left", "right", etc. are only used to indicate relative positional relationships. When the absolute position of the object being described changes, the relative positional relationship may change;

[0053] Secondly: In the drawings of the embodiments disclosed in the present invention, only the structures related to the embodiments disclosed in the present invention are involved, and other structures can refer to the general design. In the absence of conflict, the same embodiment and different embodiments of the present invention can be combined with each other;

[0054] Finally: The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a dry colloidal electrolyte for an aqueous battery, characterized in that include: 1.5 g of nano-silicon dioxide is placed in 10 ml of an aqueous solution of an electrolyte salt with a solute ratio of 0.5-3 mol / L, and stirred evenly to obtain an aqueous gel electrolyte; The obtained aqueous gel electrolyte is placed in a freeze dryer for freeze drying, and after the water content no longer changes, a dry gel electrolyte for an aqueous battery is obtained.

2. The method for preparing a dry colloidal electrolyte for an aqueous battery according to claim 1, characterized in that: The electrolyte salt is one or more of sodium sulfate, sodium nitrate, sodium perchlorate, lithium sulfate, lithium nitrate, lithium perchlorate, zinc sulfate, zinc nitrate, and zinc perchlorate.

3. The method for preparing a dry colloidal electrolyte for an aqueous battery according to claim 1, characterized in that: The particle size of the nano silicon dioxide is in the range of 5nm-500nm.

4. The method for preparing a dry colloidal electrolyte for an aqueous battery according to claim 3, characterized in that: The particle size of the nano silicon dioxide is in the range of 10nm-30nm.

5. The method for preparing a dry colloidal electrolyte for an aqueous battery according to claim 1, characterized in that: The nano silicon dioxide is hydrophilic nano silicon dioxide.

6. The method for preparing a dry colloidal electrolyte for an aqueous battery according to claim 1, characterized in that: When the freeze dryer is used for drying, the temperature is adjusted to -20°C and the freeze drying time is 8 hours.

7. An aqueous dry colloidal electrolyte prepared by the preparation method according to any one of claims 1 to 5.

8. Use of the aqueous dry colloidal electrolyte as claimed in claim 7 in the preparation of an aqueous battery, characterized in that: The aqueous dry gel electrolyte is embedded on the positive and negative electrodes or the diaphragm of the battery.